On the existence of solutions connecting singularities in nonlinear RLC circuits. (April 2015) - Battelli, Flaviano; Fečkan, Michal
Abstract: We apply dynamical system methods and Melnikov theory to study small amplitude perturbations of some implicit differential equations arising in RLC circuits. We find conditions under which solutions joining two singularities persist after a small forcing. Finally, in the last section we extend this result to a wider class of implicit differential equations.